Intravitreal bevacizumab (Avastin) therapy versus photodynamic therapy plus intravitreal triamcinolone for neovascular age-related macular degeneration: 6-month results of a prospective, randomised, controlled clinical study. Issue 3 (26th February 2008) - Weigert, G; Michels, S; Sacu, S; Varga, A; Prager, F; Geitzenauer, W; Schmidt-Erfurth, U
Abstract : Aims: To compare functional and anatomical outcomes of intravitreal bevacizumab (Avastin) and verteporfin (photodynamic) therapy (PDT) combined with intravitreal triamcinolone (IVTA) in patients with neovascular age-related macular degeneration (AMD). Methods: Twenty-eight patients with neovascular AMD were enrolled in a prospective, randomised, controlled clinical trial. All patients randomly assigned to 1 mg intravitreal bevacizumab (0.04 ml) received three initial treatments at 4-week intervals. In further follow-up retreatment was based on optical coherence tomography (OCT). Patients randomly assigned to standard PDT received a same-day intravitreal injection of 4 mg triamcinolone (Kenalog). Retreatment was based on fluorescein angiography at 3-month intervals. Functional and anatomical results were evaluated using the Early Treatment Diabetic Retinopathy Study protocol vision charts, fluorescein angiography and OCT. Results: In the bevacizumab-treated group mean visual acuity (VA) improved to a 2.2 line gain at 6 months follow-up. Eyes treated in the PDT plus IVTA group had a stable mean VA at month 6 compared with baseline. There was a statistically significant difference (p = 0.03, analysis of variance (ANOVA)) between both groups as early as one day after initial treatment. The reduction in central retinal thickness (CRT) showed no significant difference between both groups (p = 0.3, ANOVA). Mean CRT was reduced from 357 μm at baseline to 239 μm at month 6 in bevacizumab-treated patients and from 326 μm to 222 μm, respectively, in PDT plus IVTA-treated patients. No significant local or systemic safety concerns were detected up to month 6. Conclusion: Intravitreal bevacizumab showed promising 6-month results in patients with neovascular AMD. Functional outcomes appear not only to be dependent on a reduction in CRT but also on the treatment modality used.